2016
DOI: 10.1186/s12915-016-0305-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional integration of the circulatory, immune, and respiratory systems in mosquito larvae: pathogen killing in the hemocyte-rich tracheal tufts

Abstract: BackgroundAs both larvae and adults, mosquitoes encounter a barrage of immune insults, ranging from microbe-rich communities in larval habitats to ingested blood-borne pathogens in adult blood meals. Given that mosquito adults have evolved an efficient means of eliminating infections in their hemocoel (body cavity) via the coordinated action of their immune and circulatory systems, the goal of the present study was to determine whether such functional integration is also present in larvae.ResultsBy fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 78 publications
4
44
0
Order By: Relevance
“…A recently described immune phenomenon in mosquitoes relies on sessile periosteal hemocytes attached to the periosteum region of the heart (i.e., flanking the valves) to sequester and concentrate circulating microbes and pathogens (King & Hillyer, ; League & Hillyer, ; Sigle & Hillyer, ). This builds on previous observations that pathogens accumulate in discrete foci along the surface of the mosquito heart during infection (Hillyer, Barreau & Vernick, ).…”
Section: Hemocyte Roles In Melanizationmentioning
confidence: 99%
“…A recently described immune phenomenon in mosquitoes relies on sessile periosteal hemocytes attached to the periosteum region of the heart (i.e., flanking the valves) to sequester and concentrate circulating microbes and pathogens (King & Hillyer, ; League & Hillyer, ; Sigle & Hillyer, ). This builds on previous observations that pathogens accumulate in discrete foci along the surface of the mosquito heart during infection (Hillyer, Barreau & Vernick, ).…”
Section: Hemocyte Roles In Melanizationmentioning
confidence: 99%
“…In adults, this is reflected in the aggregation of haemocytes at the periostial regions, which surround the locations where haemolymph enters the heart (King & Hillyer, ; Sigle & Hillyer, ). Haemolymph circulation in larvae is different, which is reflected by the aggregation of haemocytes at the tracheal tufts that surround the sole entry point for haemolymph into the larval heart (League et al ., ; League & Hillyer, ). Here, we expanded our understanding of the biology of periostial haemocytes, and implicate two Nimrod family genes – eater and draper – in periostial immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Metamorphosis involves considerable shifts in the ecology and physiology of many invertebrates, including alterations to the immune system (League, Estevez‐Lao, Yan, Garcia‐Lopez, & Hillyer, ; League & Hillyer, ; Russell & Dunn, ). In mosquitoes, metamorphosis has decoupled the larval and adult immune systems such that immunity is strongest in larvae and declines after eclosion and with adult age (League et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The aquatic habitats of mosquito larvae are rife with microorganisms that can invade the hemocoel (body cavity) (Bartholomay & Michel, ; Granados, ; Kalucy & Daniel, ; Petersen, Chapman, & Woodard, ; Sweeney, Inman, Bland, & Wright, ; Washburn, Egerter, Anderson, & Saunders, ; Yassine, Kamareddine, & Osta, ). Consequently, mosquito larvae mount powerful cellular and humoral immune responses against pathogens in their hemocoel (Biron et al, ; Dimopoulos, Richman, Muller, & Kafatos, ; Duncan et al, ; Kalucy & Daniel, ; League et al, ; League & Hillyer, ; Meredith, Hurd, Lehane, & Eggleston, ; Richman et al, ; Shin et al, ). Recently, we demonstrated that a larval‐acquired infection in the hemocoel is transstadially transmitted to the hemocoel of an adult, which may have important implications for adult immunity (Brown, Thompson, & Hillyer, ).…”
Section: Introductionmentioning
confidence: 99%